Ensuring Support and Inclusion for Individuals with Autism Spectrum Disorder in Pakistan: Ensuring Support for Individuals with Autism Spectrum Disorder - Mehboob, Riffat (Pakistan Journal of Health Sciences, 2025)
Autism Spectrum Disorder (ASD) is a lifelong neurodevelopmental condition characterized by differences in social communication, restricted or repetitive behaviors, and atypical sensory processing. The term “spectrum” reflects the wide variation in strengths, challenges, and levels of support required by individuals with autism, ranging from those who live independently to those needing substantial assistance. As understanding of ASD has expanded globally, it has increasingly been recognized not only as a clinical condition but also as a broader social and public health concern, particularly in countries where awareness, diagnosis, and support systems remain limited [1,2]. Autism Spectrum Disorder (ASD) is among the most urgent and yet least understood social health issues in Pakistan. It influences social communication, behavior, as well as sensory processing, and children and adults display a broad spectrum of skills and disabilities. Worldwide, ASD is found in approximately 1 per 160 children and research in Pakistan shows that prevalence is similar with 1.3% of children in Karachi (2017) and 1.45% of school going children in Lahore (2019) being diagnosed with ASD. In spite of the increased awareness around the world, Pakistan still has a lot of gaps in awareness, diagnosis and care of ASD individuals [1,2]. In Pakistan, the family of children with ASD have enormous challenges in accessing the qualified professionals and evidence-based interventions. Consequently, they are left to deal with complicated behavioral, sensory and co-occurring problems in many cases without much support. This is often postponed through inconsistent screening and lack of professional capacity as a result of early diagnosis, which may greatly improve the outcome. There are also misconceptions and a dependency on untested home remedies or expensive private care and low educational inclusion of children denies them special learning settings. All of these gaps demonstrate that ASD is not merely a medical problem, but a social and even a bigger social and public health problem that requires immediate intervention [1]. The Punjab Autism Act was passed and it has given official support and recognition to the specialized schools, resource centers, research, professional training, and public awareness campaigns. Recent researches emphasize psychosocial needs of families, sensory and behavioral characteristics of children, and the significance of structured and evidence-based interventions. The focus on the early detection of ASD in regular pediatric care and the development of telehealth, as well as on building community-based support networks, such as online parent communities, offering peer support and emotional assistance is growing. These advances are significant progress in the direction of inclusive education and holistic care, and the problems of awareness, early diagnosis, and professional training still exist [3]. Although these positive steps are made, there is still much to be done. To address the problem of stigma, Pakistan needs to invest in ongoing professional training of healthcare workers, implement screening of ASD at the primary pediatric stage, and initiate mass-scale public education programs. There is an urgent need to have robust support systems to families, better access to quality diagnosis and evidence-based therapy. Studies should emphasize on culturally appropriate interventions and experiences of Pakistani families to inform effective policies. Pakistan has the potential to shift the awareness into action by connecting healthcare, education, and social services and promoting community inclusion [3,4]. The developments anticipated in 2025 may represent a critical turning point for autism care and policy in Pakistan. However, sustained, coordinated efforts across healthcare, education, and social sectors will be essential to ensure that individuals with ASD are empowered to thrive and that their families receive the long-term support, inclusion, and dignity they deserve.